Liquidity and Profitability Analysis of Selected Automobile Companies - Vikas Garg; Pooja Tiwari; Shalini Srivastava (International Journal of Supply Chain Management, 2018)
Liquidity management and Profitability of a firm is of a major importance in the current scenario majorly for financial management decision. The most accepted fiscal performance can only be achieved by organizations who can maintain a tradeoff between profitability and liquidity position of the organization. The main objective of this study is to know the importance of both of them. In this regard, researchers are interested in the study of Automobile companies. It is known that mangers can increase the profitability and sustain liquidity by working on various ratios of the companies like, Current ratio, liquidity ratio etc. It can also emphasize on maintaining the cost of goods sold and analyzing the various areas of operations in order to strengthen the financial position of the country. All financial ratios are used to assess the performance of the company but profitability ratios are helpful in calculation of the operations invested. Various liquidity ratios are also calculated for short term analysis of a business concern. Thus, we can say that profitability ratios are the major decision maker to understand the overall efficiency of an organization. Management and profitability ratios relating to investment are helpful in calculating a reasonable return on capital.